The Control of Oil Palm Plantations In Wetlands Through Spatial Planning in South Kalimantan, Indonesia in the Context of Climate Change - Muhammad Hadin Muhjad (Program Magister Hukum Universitas Lambung Mangkurat, 2016)
Policy arrangement palm plantations in peat wetlands in particular in order to guard against damage to the ecosystem. Basically peatlands can cater for oil crops if done carefully with the right technology and methods as well.In order to control oil palm plantations on peatlands can be done through the arrangement of space in addition to directing the appropriate plantations also lead to appropriate land capability.Keywords : Control, Oil Palm Plantations, WetlandsKata kunci : Pengawasan, Perkebunan Kelapa Sawit, Lahan Basah